Field notes contributed by Paul Martsching, winter 1982-1983 - Martsching, Paulet al (1982)
Winter report of birds found in central Iowa contributed by Paul Martsching. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1982-1983. Epson - sheet feed